2003
DOI: 10.1051/0004-6361:20021803
|View full text |Cite
|
Sign up to set email alerts
|

The Parkes quarter-Jansky flat-spectrum sample

Abstract: Abstract. We present optical spectra and redshift measurements for 178 flat-spectrum objects from the Parkes quarter-Jansky flat-spectrum sample. These spectra were obtained in order to compile a complete sample of quasars for use in a study of quasar evolution. We present a composite optical spectrum made from the subset of 109 quasars that have flux densities in the range 0.25 Jy < S 2.7 GHz < 0.5 Jy, and make a comparison with a composite for radio-quiet QSOs from the Large Bright Quasar Survey. Our large s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…2254À204: Previous optical spectroscopy ( Véron-Cetty & Véron 1993b;Hook et al 2003) of this BL Lac object from the 1 Jy sample showed completely featureless spectra. With the VLT we are able to detect faint interstellar absorptions of Ca ii kk3934, 3968 and Na i k5892, but no intrinsic or intervening spectral lines are found.…”
Section: Notes On Individual Objectsmentioning
confidence: 77%
See 2 more Smart Citations
“…2254À204: Previous optical spectroscopy ( Véron-Cetty & Véron 1993b;Hook et al 2003) of this BL Lac object from the 1 Jy sample showed completely featureless spectra. With the VLT we are able to detect faint interstellar absorptions of Ca ii kk3934, 3968 and Na i k5892, but no intrinsic or intervening spectral lines are found.…”
Section: Notes On Individual Objectsmentioning
confidence: 77%
“…Based on EW min , we estimate z > 0:31. 0627À199: Hook et al (2003) obtained a lineless spectrum for this radio-selected BL Lac object. Our VLT spectrum, of moderate S/ N (50), shows no spectral features.…”
Section: Notes On Individual Objectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, most of the work in this field has made use of 2−4 m class telescopes (e.g. Falomo et al 1993;Stickel & Kühr 1993;Véron-Cetty & Véron 1993;Bade et al 1994;Falomo et al 1994;Falomo 1996;Marchã et al 1996;Drinkwater et al 1997;Laurent-Muehleisen et al 1998;Landt et al 2001;Rector & Stocke 2001;Londish et al 2002;Hook et al 2003;Carangelo et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As described in detail in Jackson et al (2002) we selected all flat-spectrum sources from PKSCAT90 with oi h^z Hz > -0.4, where S ex v a , yielding an initial sample of 878 sources. Imaging and spectroscopy campaigns (Jackson et al 2002;Hook et al 2003) yielded a final sample of identifications. We found that 677/878 sources had stellar host objects (quasars and BLLac objects).…”
Section: Radio-selected Quasar Samplesmentioning
confidence: 99%